CHANGES IN THE FIELD OF AGRAG OF UZBEKISTAN IN THE 1990S (Academia Science Repository, 2023)
This article provides information about changes in the field of agrag of Uzbekistan in the 1990s and agrarian conditions , changes in Uzbekistan during the savet Union.